Unorthodox Dimensional Interpolations for He, Li, Be Atoms and Hydrogen Molecule - Ghosh, Kumar J. B.; Kais, Sabre; Herschbach, Dudley R. (Frontiers in Physics, 2020)
We present a simple interpolation formula using dimensional limits D = 1 and D = ∞ to obtain the D = 3 ground-state energies of atoms and molecules. For atoms, these limits are linked by first-order perturbation terms of electron-electron interactions. This unorthodox approach is illustrated by ground-states for two, three, and four electron atoms, with modest effort to obtain fairly accurate results. Also, we treat the ground-state of H2 over a wide range of the internuclear distance R, and compares well with the standard exact results from the Full Configuration Interaction method. Similar dimensional interpolations may be useful for complex many-body systems.